Renal Cell Carcinoma Embolization for the Treatment of Budd–Chiari Syndrome - Allison, Stephen; Johnson, Guy; Kogut, Matthew; Monroe, Eric (Journal of Clinical Interventional Radiology ISVIR, 2017)
Renal cell carcinoma (RCC) is the eighth most common malignancy, accounting for 3% of all newly diagnosed neoplasms. RCC venous invasion occurs in 4 to 10% of cases. We report a case of RCC with extensive vascular invasion and new-onset liver dysfunction. The etiology of the liver dysfunction was attributed to hepatic vein obstruction; herein we describe the first reported case of transcatheter embolization of RCC for Budd–Chiari syndrome.
Keywords: renal cell carcinoma; embolization; Budd–Chiari syndrome; Stauffer's syndrome